Plasma-treated catalyst, method of making same and use thereof

Plasma-treated metal oxide catalysts with doping metals address the limitations of existing methanol synthesis catalysts by enhancing CO2 hydrogenation and syngas desulfurization, offering improved activity and selectivity.

JP2025501962AActive Publication Date: 2025-01-24MAX PLANCK GESELLSCHAFT ZUR FOERDERUNG DER WISSENSCHAFTEN EV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024539623
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-30
Filing Date
2022-12-22
Publication Date
2025-01-24
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

Existing methanol synthesis catalysts face limitations in high CO2 concentrations, leading to decreased methanol selectivity and the need for improved catalysts that can efficiently hydrogenate CO2 to methanol with high activity and selectivity, as well as catalyze desulfurization in syngas processes.

Method used

A catalytically active material comprising a metal oxide doped with a doping metal, such as CeO2, ZnO, Ga2O3, In2O3, ZrO2, Fe2O3, or Al2O3, treated with non-thermal plasma, which stabilizes the doping metal within the oxide matrix, enhancing its catalytic performance.

Benefits of technology

The plasma-treated metal oxide catalysts exhibit improved catalytic activity, stability, and selectivity for hydrogenating CO2 to methanol and desulfurizing syngas, with enhanced surface structure and electronic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501962000001_ABST
    Figure 2025501962000001_ABST
Patent Text Reader

Abstract

The present invention relates to a catalytically active material, its preparation and its use in, for example, the catalytic hydrogenation of CO2 to methanol. The catalytically active material comprises a metal oxide doped with a doping metal, said metal oxide being selected from CeO2, ZnO, Ga2O3, In2O3, ZrO2, Fe2O3 and Al2O3, said doping metal being selected from Cu, Pd and Au, and the catalytically active material being obtained by a method comprising a step of a non-thermal plasma treatment.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application relates to catalytically active materials, their preparation, and uses of the catalytically active materials. [Background technology]

[0002] In view of dwindling fossil fuel resources and the threat of climate change, sustainable and environmentally friendly production of methanol is important. Methanol can be produced from H2 (green H2 can be produced by electrolysis via water split) and the greenhouse gas CO2. Today, the synthesis of methanol is carried out from a mixture of H2, CO, and CO2 over a Cu / ZnO / Al2O3 catalyst (M. Bukhtiyarova et al., Catal. Letters 147, 416 (2017)). In this method, the CO2 concentration in the starting gas mixture is limited to a maximum of about 10%. It has been observed that the methanol selectivity decreases with increasing concentrations of CO2 (J. Zhong et al., Chem. Soc. Rev. 49, 1385 (2020)). For this reason, there is a demand for catalysts that can hydrogenate CO2 to methanol with high reaction rates and high methanol selectivity.

[0003] There is also a continuing need for active materials to catalyze the reverse water gas shift reaction (CO2+H2→CO+H2O; see Y. Daza, JN Kuhn, RSC Advances 6, 49675 (2016)), or the desulfurization of CO2 feed or synthesis gas containing CO, H2, and CO2, where conventional Cu / ZnO catalysts are used (M. Breysse et al., Catalysis Today 84, 129 (2003); J. W. Bae et al., Int. J. Hydrogen Energy 34, 8733 (2009)). Summary of the Invention [Problem to be solved by the invention]

[0004] It is an object of the present invention to provide catalytically active materials that can be effectively used to catalyze the hydrogenation of CO2 to methanol, and / or other industrially relevant processes, such as the reverse water gas shift reaction or the desulfurization of synthesis gas or CO2 feed. Another object is to provide catalytically active materials suitable for the hydrogenation of CO2 to methanol, and / or other industrially relevant processes, which show high activity, high selectivity and / or stability in the corresponding reactions. In one alternative embodiment, it is another object of the present invention to provide a simple and effective method for preparing such catalytically active materials that can be suitably used in the present processes. [Means for solving the problem]

[0005] The present inventors have found that the above problems can be solved by the following embodiments (hereinafter, referred to as "matters"). [Matter 1] A catalytically active material comprising a metal oxide doped with a doping metal, the metal oxide is selected from CeO2, ZnO, Ga2O3, In2O3, ZrO2, Fe2O3, Al2O3; the doping metal is selected from Cu, Pd, Au; The catalytically active material is obtainable by a process including a non-thermal plasma treatment step. [Matter 2] 2. The catalytically active material according to item 1, wherein the metal oxide is In2O3. [Matter 3] 3. The catalytically active material according to claim 1 or 2, wherein the doping metal is Cu. [Matter 4] 4. The catalytically active material according to any one of claims 1 to 3, wherein the content of the doping metal relative to the metal oxide is between 0.01 wt% and 5.0 wt%, preferably between 0.01 wt% and 3.0 wt%, more preferably between 0.05 wt% and 0.3 wt%. [Matter 5] 5. The catalytically active material according to any one of claims 1 to 4, in the form of particles. [Matter 6] 6. The catalytically active material according to item 5, wherein the catalytically active material is composed of the metal oxide, the doping metal and optional negatively charged counter ions. [Matter 7] 7. The catalytically active material according to item 5 or 6, wherein the catalytically active material has an average particle size of 5 nm to 50 nm as measured by transmission electron microscopy (TEM) or scanning transmission electron microscopy (STEM). [Matter 8] 5. The catalytically active material according to any one of claims 1 to 4, in the form of a membrane. [Matter 9] 9. Use of the catalytically active material according to any one of items 1 to 8 in the catalytic hydrogenation of CO2 to methanol by reacting a gas mixture composed of H2 and CO2. [Matter 10] 10. The use according to item 9, wherein the mixed gas comprising H2 and CO2 is reacted in the presence of the catalytically active material at a pressure of 10 bar to 150 bar and a reaction temperature of 100°C to 400°C, preferably 150°C to 350°C. [Matter 11] 11. The use according to item 9 or 10, wherein the mixed gas has a H2 / CO2 molar ratio of 3.0 or more, preferably 3.5 or more. [Matter 12] A method for producing a catalytically active material according to any one of claims 5 to 7, comprising the steps of: (1) co-precipitating the doping metal and the metal component of the metal oxide as hydroxides by adding an alkaline solution (e.g., a Na2CO3 solution) to an aqueous solution containing salts of the doping metal and the metal component of the metal oxide; (2) washing and drying the precipitate; (3) calcining the dried precipitate in the presence of O2; (4) subjecting the calcined precipitate to a non-thermal plasma treatment to obtain particles of the catalytically active material; The method comprising: [Matter 13] 13. The method according to item 12, wherein the non-thermal plasma treatment is carried out at a pressure of 40 mbar or less. [Matter 14] Item 9. A method for producing a catalytically active material according to item 8, comprising the steps of: (1) providing a film comprising said metal of said metal oxide and said doping metal, preferably by a co-deposition method; (2) annealing the film in the presence of oxygen; (3) performing a non-thermal plasma treatment; The method comprising:

[0006] When this specification refers to preferred embodiments / features, regardless of their level of preference, a combination of these preferred embodiments / features is considered to be disclosed as long as this combination of preferred embodiments / features makes technical sense.

[0007] As used herein, the use of the terms "having" or "including" means Insofar as it is technically meaningful, the term "consisting of" should also be understood as disclosing more limited embodiments.

[0008] When preferred upper and lower limits are given for certain features, this should be understood to disclose any combination of the upper and lower limits.

[0009] Hereinafter, depending on the context, the term "catalytically active material" may be interchangeable with "catalyst." [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram of the experimental setup used for plasma treatment of catalytically active materials in the form of films (a) and nanoparticle powders (b). [Diagram 2]FIG. 1 shows methanol production rates measured after 1 hour (a) and 24 hours (b) over untreated and plasma-treated Cu-In2O3 catalysts and Cu-free In2O3 catalysts from Comparative Examples 1 to 4, Reference Example 1, and Examples 1 to 3 (CO2:H2:He=1:4:1, 60 bar, 48 mL / min, 280° C.). [Diagram 3] Reaction rates measured over Cu-In2O3 catalyst containing 0.1 wt% Cu according to Examples 1, 4 and 5 (CO2:H2:He=1:4:1, 60 bar, 48 mL / min, 280°C). [Figure 4] Fourier transform Cu K-edge extended X-ray absorption fine structure (EXAFS) spectra of Cu-In2O3 catalysts according to Example 1 ("plasma treatment") and Comparative Example 1 ("calcination"). Spectra were recorded for each catalyst without any treatment (as-prepared) and after CO2 hydrogenation reaction (post-reaction) in a mixture of CO2+H2+He (1:4:1) at 280°C and 60 bar total pressure. The fractional contribution of Cu-Cu bonds obtained from the nonlinear least-squares EXAFS data fitted to the catalysts used is shown by the dashed line. The spectra have been shifted vertically for clarity. [Diagram 5] 1A and 1B show scanning tunneling microscope images of an In2O3 film catalyst (Reference Example 2) and a plasma-treated In2O3 film catalyst (Reference Example 3), and topography profiles (c, d) along the lines indicated in the corresponding images (a, b). [Figure 6] 1 shows the O1s region of X-ray photoelectron spectra measured for catalysts according to Reference Example 2 (In2O3 untreated), Reference Example 3 (In2O3 plasma), Comparative Example 5 (Cu-In2O3 untreated), and Example 6 (Cu-In2O3 plasma). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] I. Catalytic active material The catalytically active material of the present invention comprises a metal oxide doped with a doping metal. The metal oxide is selected from CeO2, ZnO, Ga2O3, In2O3, ZrO2, Fe2O3 and Al2O3. The doping metal is selected from Cu, Pd and Au. The catalytically active material is obtained by a method including a non-thermal plasma treatment step. The method comprises, for example, a step of co-depositing a metal oxide with a doping metal to obtain a precursor and calcining the precursor.

[0012] By "atomically dispersed" is meant the presence in the catalytically active material, and, if necessary, also at the surface of the catalytically active material, of single doping metal atoms (also called "dopants"), which can be detected by conventional analytical techniques, such as extended X-ray absorption fine structure (EXAFS), infrared spectroscopy (IR), or STEM. For the avoidance of doubt, and unless otherwise stated, the use of the term "atom" in the specification and claims covers both neutral (oxidation state=0) and charged (ionic, e.g., oxidized) doping metal atoms.

[0013] The form of the catalytically active material is not particularly limited. For example, it may be in the form of particles (e.g., powder) or a film.

[0014] To optimize its usefulness in industrial processes, the catalytically active material may be applied (supported) to an inert support material. When the catalytically active material is present as a membrane, it may be supported by a suitable planar support material.

[0015] The present invention is characterized in that catalytically active materials are obtained by a method including a step of non-thermal plasma treatment. In the present invention, it is preferable to start with a material in which the dopant metal atoms are incorporated inside the metal oxide (also called "metal oxide matrix") of the catalytically active material. In particular, it is believed that the effect of the plasma treatment is to stabilize the initial "as prepared" state of the doped metal oxide material, with the doping metal atoms remaining mostly inside the host metal oxide matrix. Without wishing to be bound by theory, it is believed that if the doping metal atoms migrate from inside the metal oxide matrix to its surface under reaction conditions, they have a lower mobility at the metal oxide surface due to its greater plasma-enhanced roughness. On the other hand, in the reference catalyst prepared without plasma treatment, more doping atoms reach the surface (leave the matrix) under reaction conditions, and then sintering occurs. This gives rise to an X-ray absorption spectrum (XAS) for example a metallic Cu-Cu signal, which corresponds to the formation of relatively large particles, in contrast to having the doping metal atoms dispersed in In2O3 (or other claimed metal oxides) or forming very small clusters.

[0016] In one embodiment, the catalytically active material of the present invention exhibits additional states of O atoms, characterized by a binding energy of the O1s core level that is 1.4 eV to 2.5 eV, preferably 1.6 eV to 2.2 eV higher than that of the main signal of the metal oxide, as observed by X-ray photoelectron spectroscopy (XPS). See also FIG. 6. The XPS analysis can be performed according to the method described in the Examples. This additional XPS signal can be observed as a shoulder of the main signal. Without being bound by theory, the additional XPS signal is due to oxygen from defect sites, which are preferably formed on the surface of the metal oxide during the non-thermal plasma treatment. For example, in the case of In2O3, the O1s XPS signal of In2O3 appears at 530.2 eV and the signal of oxygen from defect sites appears at 532.0 eV.

[0017] In this embodiment, the intensity of the additional signal is preferably at least 30% of the intensity of the main peak, more preferably at least 40%.

[0018] In one embodiment, the non-thermal plasma treatment results in the formation of metal oxide nanoclusters on the surface of the catalytically active material. The average diameter of the metal oxide nanoclusters may be 4.0 nm or less, preferably 2.5 nm or less, as measured by scanning tunneling microscopy (STM). See further below. STM measurements can be performed as described in the Examples.

[0019] The catalytically active material of the present invention preferably exhibits one or more of the properties described in the above embodiments.

[0020] In the present invention, the catalytically active material comprises a metal oxide doped with a doping metal, and the metal oxide is selected from CeO2, ZnO, Ga2O3, In2O3, ZrO2, Fe2O3, and Al2O3. The metal oxide is preferably selected from ZnO, ZrO2, Ga2O3, In2O3, and Al2O3, more preferably selected from ZnO, ZrO2, and In2O3, and most preferably In2O3. The metal oxide may be used alone or in combination of two or more kinds.

[0021] In the present invention, the doping metal used to dope the metal oxide is selected from Cu, Pd, Au. The metal is preferably Cu. In a preferred embodiment, the "doping" metal atoms are atomically dispersed in the host material (metal oxide matrix).

[0022] Preferably, the doping metal is present in the (as-prepared) catalytically active material as a single atom (ion) incorporated in the corresponding metal oxide matrix (e.g., Cu in In2O3). The doping metal is preferably present in the as-prepared catalytically active material in a positive oxidation state (X), i.e., in an oxidized form. In one embodiment, X is 2+ for Cu and Pd, and 3+ for Au. It is noted that the oxidation state may depend on various factors. In the case of Cu-In2O3, Cu substitutes for In 3+, but may be in the 2+ state, for example. To balance the net charge, this process may be performed by creating an O vacancy or placing a counter ion nearby.

[0023] Due to the doping metal doped into the metal oxide, the catalytically active material of the present invention can exhibit excellent catalytic activity in CO2 hydrogenation reaction to methanol and / or CO (reverse water gas shift) and / or desulfurization of CO2 or syngas (CO+CO2+H2). Without being bound by theory, it is presumed that the electronic structure of the metal oxide is modified in the presence of the metal dopant, resulting in a superior ability in activating reactants. Furthermore, it is presumed that the presence of the metal dopant modifies the crystal structure of the metal oxide, inducing a high surface energy of the metal oxide, which also aids in activating the reactants.

[0024] The combination of metal oxide and doping metal is not particularly limited. In a preferred embodiment, the metal oxide is selected from CeO2, ZnO, Ga2O3, In2O3, and Al2O3, and the doping metal is selected from Cu, Pd, or Au. The combination of In2O3 and Cu is more preferred.

[0025] The amount of the doping metal relative to the metal oxide is not particularly limited, but is preferably 0.01 wt% to 5.0 wt%, more preferably 0.01 wt% to 3.0 wt%, and even more preferably 0.01 wt% to 1.0 wt%. The amount of the doping metal relative to the metal oxide is particularly preferably 0.05 wt% to 0.3 wt%, since it can further increase the CO2 hydrogenation activity of the catalytically active material.

[0026] The atmosphere in which the non-thermal plasma treatment is performed is not particularly limited, but is at least one selected from N2, O2, and Ar, and is preferably O2. Preferably, the non-thermal plasma treatment is performed in the presence of at least O2.

[0027] In the first embodiment of the present invention, the catalytically active material is present in the form of particles, for example, may be formed as a powder. The shape of the particles is not particularly limited and may be selected from, for example, ellipsoidal, cubic, spherical, etc.

[0028] In the first embodiment of the present invention, the average particle size of the catalytically active material is not particularly limited, but is preferably 5 nm to 1 μm, more preferably 5 nm to 500 nm, even more preferably 5 nm to 100 nm, and particularly preferably 5 nm to 50 nm. The average particle size of the metal oxide substrate can be determined by measuring the particle size of 20 arbitrarily selected particles by a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM) and calculating the average. The longest visible axis of the particle is taken as the "diameter". If it is desired to further increase the measurement accuracy, the measurement can be performed on 100 arbitrarily selected particles. The detailed method is described in the Examples section. In the case where multiple particles are agglomerated with each other, the particle size of the primary particles is taken as the measurement.

[0029] In a first embodiment of the invention, the catalytically active material is preferably composed of said metal oxide and said doping metal. If the doping metal is present in the form of metal ions, (negatively charged) counterions may also be present to balance the net charge. These counterions may for example come from the salt of the doping metal used in the preparation of the catalytically active material.

[0030] In a second embodiment of the invention, the catalytically active material is in the form of a membrane.

[0031] The catalytically active material may also be provided as a film on a substrate (substrate). In one embodiment, the substrate provides a flat substrate, and the catalytically active material film can be provided on the substrate, for example, by deposition of metal oxide precursors and metal precursors, followed by an oxidation step. The substrate is not particularly limited as long as it does not adversely affect the catalytically active material. For example, substrates made of metals, alloys, and ceramics may be used. Metals used as substrates may be single crystals, and may include, for example, Ru(0001) single crystals. Examples of alloys that can be used as substrates include, but are not limited to, steel, brass, and the like. Ceramics that can be used as substrates include, but are not limited to, silica, silicon carbide, and the like. Those skilled in the art can select a substrate suitable for the reaction conditions to which the catalytically active material (coating layer) will be exposed.

[0032] In the second embodiment of the present invention, the thickness of the catalytically active material film is not particularly limited, but is preferably 5 nm to 50 nm, more preferably 5 nm to 20 nm. The thickness of the catalytically active material film can be determined, for example, by measuring the attenuation of the XPS signal of the substrate on which the catalytically active material film is provided, using XPS. For example, when a catalytically active material film is provided on a Ru substrate, the attenuation of the Ru3d signal in the XPS spectrum can be measured to determine the thickness of the catalytically active material film. Similarly, when a silica-based material is used, the attenuation of the Si2p signal in the XPS spectrum can be used. Those skilled in the art can appropriately select the signal arising from the element in the substrate, measure its attenuation, and determine the thickness of the catalytically active material film.

[0033] In a second embodiment of the present invention, the catalytically active material film can have metal oxide clusters present on the film surface, which may have the same metal oxide. The average diameter of the clusters is 4.0 nm or less, preferably 2.5 nm or less, which may be determined by plotting the topographical profile with a scanning tunneling microscope (STM) along a line corresponding to a length of, for example, 10 nm, measuring the distance between two adjacent minima, multiplying the measurement by a correction factor of 0.5, recording the obtained value as the diameter, repeating the measurement for 20 arbitrarily selected surface areas showing coverage by metal oxide clusters, and calculating the average value. A detailed method is described in the Examples section.

[0034] The number of clusters supported on the film surface and normalized per unit area of ​​the metal oxide substrate (surface cluster density) is not particularly limited. The surface cluster density is preferably at least 0.03 clusters / nm 2 , more preferably at least 0.05 clusters / nm 2 , and more preferably at least 0.08 clusters / nm 2 , most preferably at least 0.10 clusters / nm 2 The surface cluster density can be determined by STM by counting the number of metal oxide clusters present in an arbitrarily selected area. Detailed methods are described in the Examples section.

[0035] The catalytically active material of the present invention is particularly suitable for catalyzing the hydrogenation of CO2.

[0036] The catalytically active materials of the present invention exhibit excellent stability and activity in the hydrogenation of CO. It is presumed that, at least in part, these properties are related to the plasma treatment, which to some extent modifies the surface structure and / or electronic state of the metal oxide, suppressing the formation of large metal clusters (e.g., by agglomeration or sintering) and stabilizing or enhancing the high dispersion of the doping metal during the catalytic reaction.

[0037] The catalytically active material of the present invention can be prepared by the following method.

[0038] II. Methods for Producing Catalytically Active Materials A method for producing a catalytically active material according to a first embodiment of the present invention comprises the steps of: (1) co-precipitating the doping metal and the metal component of the metal oxide as hydroxides by adding an alkaline solution (e.g., a Na2CO3 solution) to an aqueous solution containing a salt of the doping metal and the metal component of the metal oxide; (2) washing and drying the precipitate; (3) calcining the dried precipitate in the presence of O2; (4) treating the calcined precipitate with a non-thermal plasma to obtain particles of catalytically active material; may have the following structure:

[0039] In step (1), the salt of the doping metal is not particularly limited, and examples thereof include, but are not limited to, nitrates, chlorides, sulfates, acetates, acetylacetonates, tetraamine salts (e.g., tetraamine copper(II) sulfate, tetraamine palladium(II) chloride, etc.), tetrachloroaurate(III), etc.

[0040] In step (1), the salt of the metal element of the metal oxide is not particularly limited, and examples thereof include, but are not limited to, nitrates, chlorides, sulfates, acetates, acetylacetonates, and tetraamine salts.

[0041] In step (1), the alkaline solution is not particularly limited as long as it increases the pH of the aqueous solution containing the salt of the doping metal and the metal component of the metal oxide by adding it, and examples thereof include, but are not limited to, alkaline aqueous solutions such as Na2CO3, K2CO3, NaOH, KOH, Mg(OH)2, Ca(OH)2, and CaCO3.

[0042] As used herein, the terms "calcining" or "calcination" refer to the heat treatment of a solid at high temperature in the presence of dry O2. As used herein, the term "dry" means that no additional water is introduced into the atmosphere in which the calcination takes place. For example, calcination in air is understood to take place under dry conditions.

[0043] Calcination of the precursor of the catalytically active material is preferably carried out at a temperature of 200° C. to 700° C., more preferably at a temperature of 200° C. to 600° C., even more preferably at a temperature of 250° C. to 500° C. Calcination is preferably carried out at an O2 concentration of 5 vol.% or more, more preferably at 10 vol.% or more. For example, air can be used as the O2 source.

[0044] The non-thermal plasma treatment is carried out on the calcined catalytically active material. Before ignition of the plasma, the pressure is preferably reduced to 40 mbar or less, more preferably 20 mbar or less. The pressure during the non-thermal plasma treatment is preferably 40 mbar or less, more preferably 20 mbar or less. The atmosphere in which the non-thermal plasma treatment is carried out is not particularly limited, but is one or more selected from N2, O2, and Ar, and is preferably O2. Preferably, the non-thermal plasma treatment is carried out in the presence of at least O2.

[0045] The non-thermal plasma treatment may be carried out in a static atmosphere or in a gas flow, the latter being preferred. When the non-thermal plasma treatment is carried out in a gas flow, the calcined precursor for the catalytically active material is preferably blown up (floated) by the gas flow during the non-thermal plasma treatment.

[0046] The source of the non-thermal plasma is not limited to, for example, inductively coupled plasma, capacitively coupled plasma, DC glow discharge, microwave plasma, radio frequency plasma, cold plasma jet, and dielectric barrier discharge plasma. The source of the non-thermal plasma is preferably a microwave plasma or a radio frequency plasma.

[0047] When the source of the non-thermal plasma is a microwave plasma, the anode voltage of the plasma source is preferably 0.2 kV to 2 kV, and the emission current is preferably 0.1 μA to 1 μA.

[0048] When the source of the non-thermal plasma is a high frequency plasma, the power of the high frequency plasma generator is preferably 20W to 300W.

[0049] The time for the non-thermal plasma treatment can be appropriately adjusted as desired, and is usually 1 to 300 minutes, preferably 5 to 180 minutes, more preferably 10 to 120 minutes, and further preferably 30 to 90 minutes.

[0050] A method for producing a catalytically active material according to a second embodiment of the present invention comprises the steps of: (1) providing a film comprising a metal component of a metal oxide and a doping metal, preferably by a co-deposition method; (2) annealing the film in the presence of oxygen; (3) performing a non-thermal plasma treatment; has.

[0051] In step (1), the method for providing the film containing the metal oxide doped with the doping metal is not particularly limited, and any conventionally known method may be used. Examples include, but are not limited to, co-deposition, sol-gel method, spin coating, etc., and the co-deposition method is preferred.

[0052] In step (2), the annealing is preferably carried out at a temperature of 200° C. to 400° C., more preferably 250° C. to 350° C., and even more preferably 280° C. to 320° C. The annealing is carried out at a temperature of 10 -4 It is preferably carried out in O2 at a pressure of 1000 mbar or more.

[0053] In step (3), the non-thermal plasma treatment may be carried out as described in the method for producing a catalytically active material according to the first embodiment of the present invention.

[0054] III. Catalysis The catalytically active material of the present invention can be used in at least one of the following reactions: (i) hydrogenation of CO2 to methanol (also referred to as "catalytic hydrogenation"), (ii) reverse water gas shift reaction (CO2+H2→CO+H2O), or (iii) desulfurization of a synthesis gas (CO+CO2+H2) or CO2 feed. The CO2 feed may originate, for example, from an industrial source such as a steel mill, a waste incineration plant, or a cement plant.

[0055] In a preferred embodiment, the catalytically active material of the present invention is suitable for use in the catalytic hydrogenation of CO2 to methanol. In the catalytic hydrogenation of CO2 to methanol, a reaction gas mixture containing H2 and CO2 is reacted in the presence of the catalytically active material to produce methanol. The pressure of the reaction gas mixture is not particularly limited, but is, for example, 10 bar to 300 bar, preferably 20 bar to 100 bar, more preferably 30 bar to 80 bar.

[0056] The reaction temperature of the catalytic hydrogenation is not particularly limited, but may be from 100°C to 400°C, and preferably from 150°C to 350°C.

[0057] The composition of the reaction gas mixture is not particularly limited as long as it contains CO2 and H2. The H2 / CO2 molar ratio of the reaction gas mixture is, for example, 3.0 or more, preferably 3.5 or more, and more preferably 4.0 or more. The content of CO2 in the reaction gas mixture is not particularly limited, but is, for example, 3 volume % to 25 volume %, preferably 5 volume % to 22 volume %, and more preferably 10 volume % to 20 volume %.

[0058] The reactive gas mixture may further include an inert gas, examples of which include N2, He, Ar, and the like.

[0059] (Example) The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0060] (Analysis method) Scanning Transmission Electron Microscope (STEM) Scanning transmission electron microscopy (STEM) images of the powder catalysts were recorded on a JEOL JEM ARM200F probe / image corrector TEM (JEOL) at 200 kV.

[0061] The average particle size of the catalytically active material was determined by measuring the particle size of 100 randomly selected particles and calculating the average. For selected particles, if the STEM image showed a non-spherical shape, the longest axis was taken as the diameter.

[0062] (X-ray photoelectron spectroscopy (XPS)) XPS spectra were measured on a Phoibos 150 analyzer (SPECS GmbH) using an AlKα X-ray source (hν = 1486.6 eV). Spectral analysis (background subtraction and deconvolution) was performed using the commercially available CasaXPS software (Casa Software Ltd; version 2.3.18) and the measured spectra were subjected to background subtraction using a Shirley background. O1s core level spectra were recorded with a transmission energy of 20 eV. Those skilled in the art can use their common general knowledge to assign binding energies to chemical species. For example, a tabular listing of binding energies, such as the NIST X-ray photoelectron spectroscopy database, belongs to the common general knowledge of those skilled in the art.

[0063] (X-ray Absorption Spectroscopy (XAS)) Cu K-edge (8979 eV) X-ray absorption spectra (XAS) were measured in total fluorescence yield mode at the ALBA beamline synchrotron radiation facility, Spain, using a four-channel Si drift detector. Measurements were performed at room temperature in air for the catalytically active material in the "as-prepared" state, and at 280 °C in CO2+H2+He (1:4:1) at 60 bar (total) for the catalytically active material after CO2 hydrogenation reaction, as described below. Extended X-ray absorption fine structure (EXAFS) spectra were fitted using the FEFFIT code to model the contributions derived from Cu-Cu and Cu-O bonds, respectively, using theoretical backscattering amplitudes and phases calculated via the FEFF8 code for the reference materials (i.e. Cu, CuO).

[0064] (Scanning Tunneling Microscope (STM)) STM measurements of In2O3(0001) films grown on Ru(111) were carried out at a sample bias of 1.8 V and a tunneling current of 0.2 nA.

[0065] To determine the average diameter of metal oxide clusters formed on the surface by plasma treatment, the topographical profile was plotted along a line with a length of approximately 10 nm. In the topographical profile, the distance between two adjacent minima was measured, and the measured value was multiplied by an experimentally derived correction factor of 0.5 to correct for the tip / cluster folding effect. At least 20 randomly selected metal oxide clusters were measured, and the average corrected value was calculated and used as the "cluster diameter".

[0066] To determine the surface density of metal oxide clusters, i.e. the number of metal oxide clusters normalized per unit area of ​​the membrane substrate, the number of metal oxide clusters in arbitrarily selected areas of 100 nm × 100 nm in the recorded STM images was counted. These measurements were performed on five different sample spots. The average value was taken as the "density of metal oxide clusters."

[0067] (CO2 hydrogenation reaction on catalytically active materials) The reactivity of catalytically active materials in CO2 hydrogenation reactions was measured in a tubular packed bed reactor. 100 mg of catalytically active materials and 100 mg of TiO2 (Alfa Aesar) were physically mixed and the resulting mixture was loaded into the reactor. TiO2 was inactive in the reaction and was used for dilution. The catalytically active materials were heated at 280 °C for 1 h in 60 bar of He (20 mL / min). The heated catalytically active materials were then cooled to room temperature in a He gas flow, after which the gas flow was replaced by a reaction mixture consisting of CO2, H2 and He (CO2:H2:He = 1:4:1, 48 mL / min, space flow velocity GHSV = 28800 mL / g). catalyst / h). The pressure was increased to 60 bar and the reduced catalytically active material was heated to 280° C. At the reactor outlet the gas mixture was analyzed by gas chromatography (Agilent Technologies 7890B).

[0068] (Powder catalyst) Comparative Examples 1 to 3: Preparation of Untreated Cu-In2O3 Catalyst The as-treated Cu-In2O3 catalyst was prepared according to the process shown below.

[0069] 1) In(NO3)3·xH2O (Sigma Aldrich) and Cu(NO3)2·2.5H2O (Alfa Aesar) were dissolved in deionized water (50 ml) in a round-bottom flask (250 ml) to obtain a precursor solution. The amount of In(NO3)3·xH2O used was 2.167 g, and the amount of Cu(NO3)2·2.5H2O was varied as shown in Table 1 below. 2) Na2CO3 (10.0 g) was dissolved in deionized water (100 ml) and the resulting Na2CO3 solution was added dropwise to the precursor solution while stirring at room temperature. The Na2CO3 solution was added until the pH reached 9.2. The precursor solution then became turbid due to the formation of In(OH)3 and Cu(OH)2. The slurry was left for 1 h and then 50 ml of deionized water was added. 3) The slurry was centrifuged for 5 minutes to separate the precipitate, which was then redispersed in deionized water (50 ml) and washed, then centrifuged for 5 minutes. This procedure was repeated five times to remove the remaining sodium salts. 4) The precipitate was dried in air (70°C, overnight) and calcined at 300°C for 3 hours.

[0070] The amount of Cu(NO3)2·2.5H2O used in the preparation method and the Cu content of the catalyst are shown in Table 1. The average particle size in the catalyst determined by STEM was 15 ± 2 nm.

[0071] [Table 1] Comparative Example 4: Preparation of Untreated In2O3 Catalyst The untreated In2O3 catalyst was obtained in the same manner as in Comparative Example 1, except that Cu(NO3)2·2.5H2O was not used. The average particle size measured by STEM was 8±1 nm.

[0072] (Examples 1 to 5: Preparation of plasma-treated Cu-In2O3 catalyst) In the same manner as in Comparative Examples 1 to 3, an untreated Cu-In2O3 catalyst was obtained.

[0073] Next, according to the method described below, each Cu-In2O3 catalyst was subjected to plasma treatment in the presence of O2 to obtain a plasma-treated Cu-In2O3 catalyst.

[0074] The plasma treatment was carried out in an apparatus consisting of a glass tube with a frit, a funnel-shaped glassware, a mechanical pump, a high-frequency plasma generator, and a high-voltage power supply. The glass tube was covered with a Cu mesh and connected to a high-voltage power supply. The frit was able to hold the calcined powder while allowing gas (here O2 was used) to be blown in from the bottom. The funnel-shaped glassware connected to the top of the tube and the other three outlets of the funnel-shaped glassware were connected to a pressure gauge, a mechanical pump, and a tungsten rod for grounding. The tungsten rod extended to the bottom of the glass tube, and a uniformly distributed plasma was achieved. A schematic diagram of the setup for plasma treatment is shown in Figure 1b.

[0075] The plasma was generated with a high voltage power supply (PVM500) at 20 to 60 kHz. The peak voltage was measured with an oscilloscope equipped with a high voltage probe, and the power of the plasma was the product of the root mean square (RMS) voltage and the RMS current, which were measured with a multimeter. The power and frequency output of the powder feed were adjusted until a plasma with the desired power was formed.

[0076] The conditions for the plasma treatment are as follows. 1) Untreated Cu-In2O3 powder catalyst (amount of 100 to 300 mg) was introduced into a glass tube, and the tube was evacuated to below 20 mPa. 2) Oxygen was circulated through the bottom of the tube using a flow rate of 20 mL / min O2 set by a mass flow controller (MFC). 3) The powder sample began to float in the turbulent flow. 4) The plasma was ignited. The power output and frequency of the power supply were adjusted to achieve the target power shown in Table 2. 5) The plasma treatment time was 1 hour.

[0077] The untreated Cu-In2O3 catalyst used for the plasma treatment, the target power of the plasma treatment, and the Cu content of the catalyst are shown in Table 2. The average particle size of the catalyst measured by STEM was 16 ± 2 nm.

[0078] [Table 2] (Reference Example 1: Preparation of plasma-treated In2O3 catalyst) The untreated In2O3 catalyst of Comparative Example 4 was plasma-treated to prepare a plasma-treated In2O3 catalyst in the same manner as in Examples 1 to 3. The average particle size measured by STEM was 10 nm.

[0079] (Evaluation of Results) As used herein, the "untreated" catalyst is also referred to as a "calcined" catalyst.

[0080] The prepared Cu-In2O3 catalyst had an average diameter of 16±2 nm as measured by STEM. The general morphology of the catalyst was not affected by the plasma treatment under the conditions used.

[0081] The CO2 hydrogenation activity of the prepared catalytically active materials was measured as described above. Figure 2a shows the methanol production rates measured 1 hour after the reaction temperature of 280°C was reached for the (Cu-)In2O3 catalysts in Comparative Examples 1-4, Reference Example 1, and Examples 1-3. As can be seen, for the untreated (Cu-)In2O3 catalysts in Comparative Examples 1-4, a higher methanol production rate was observed at a higher Cu loading. The plasma-treated Cu-free In2O3 catalyst in Reference Example 1 showed a lower methanol production rate than the untreated In2O3 catalyst in Comparative Example 4. In contrast, the plasma-treated Cu-In2O3 catalysts in Examples 1-3 showed a higher methanol production rate than the untreated Cu-In2O3 catalysts in Comparative Examples 1-3 at the same Cu loading. The increase in methanol production rate by O2-plasma treatment was especially noticeable at 0.1 This was evident at low wt% Cu loading.

[0082] FIG. 2b shows the methanol production rates measured 24 hours after reaching the reaction temperature of 280° C. for the (Cu-)In2O3 catalysts of Comparative Examples 1-4, Reference Example 1, and Examples 1-3. As can be seen, the untreated Cu-In2O3 catalysts of Comparative Examples 1-3 showed higher methanol production rates than the untreated In2O3 catalyst of Comparative Example 4. Among the untreated (Cu-)In2O3 catalysts of Comparative Examples 1-4, the highest methanol production rate was observed at a Cu loading of 0.5 wt%. The plasma-treated In2O3 catalyst of Reference Example 1 showed a lower methanol production rate than the pristine In2O3 catalyst of Comparative Example 4. In contrast, the plasma-treated Cu-In2O3 catalysts of Examples 1-3 showed higher methanol production rates than the untreated Cu-In2O3 catalysts of Comparative Examples 1-3 at the same Cu loading. The increase in methanol production rate by O2-plasma treatment was particularly noticeable at a Cu loading of 0.1 wt%.

[0083] Figure 3 shows the measured reaction rates for Cu-In2O3 catalysts containing 0.1 wt% Cu according to Examples 1, 4 and 5, with the target power of the plasma treatment varying from 100 W to 200 W. As the power of the plasma increased from 100 to 200 W, the reaction rate gradually increased.

[0084] FIG. 4 shows the Fourier transformed Cu K-edge EXAFS spectra for the Cu-In2O3 catalysts prepared according to Example 1 (plasma treatment) and Comparative Example 1 (calcination). Measurements were performed on the "as-prepared" catalyst and on the catalyst after carrying out the CO2 hydrogenation reaction at 280° C. in CO2+H2+He (1:4:1) at 60 bar (total) as described above ("Post-reaction"). The measured spectra of the "as-prepared" Cu-In2O3 catalyst before O2-plasma pretreatment and the Cu-In2O3 catalyst after treatment show a similar structure, which is dominated by the Cu-O distance in the first coordination shell. Another contribution to the Cu K-edge EXAFS spectrum of the as-prepared sample is observed at about 3.5 Å, the position of which is similar to that corresponding to the In-In contribution in In2O3. The presence of this feature is therefore assigned to the Cu substitution of In atoms in the In2O3 lattice. After the reaction, the calcined Cu-In2O3 catalyst showed a significant number of Cu-Cu bonds, suggesting the aggregation of Cu atoms, whereas the plasma-treated Cu-In2O3 sample retained the Cu-O bonds. The Cu-O and Cu-Cu coordination numbers obtained from fitting the EXAFS data are shown in Table 3 below. The uncertainties in the last digits are shown in brackets. The spectra of all samples were fitted simultaneously with the constraint that the bond lengths and disorder factors of the Cu-O and Cu-Cu bonds were the same in all spectra. The obtained Cu-O bond length was 1.944 ± 0.006 Å, and the obtained Cu-Cu bond length was 2.542 ± 0.006 Å, with the corresponding disorder factors of 0.005 ± 0.006 Å, respectively. 2 and 0.007 ± 0.002 Å 2 The correction of the photoelectron reference energy (ΔE0) obtained by fitting, as well as the R-factor value of the fitting, are also shown in Table 3.

[0085] [Table 3] This result represents a difference between plasma-treated and calcined Cu-In2O3 samples after reaction under identical conditions and confirms that plasma treatment can suppress the aggregation of Cu atoms that can segregate on the surface of the doped metal oxide during catalytic operation.

[0086] (membrane catalyst) (Reference Example 2: Preparation of In2O3 membrane catalyst) The experiments were carried out in an ultra-high vacuum (UHV) chamber equipped with a low energy electron diffraction (LEED), an X-ray photoelectron spectrometer (XPS), and a scanning tunneling microscope (STM), all available from SPECS GmbH. Ordered In2O3(111) films were grown on Ru(0001) single crystals by the following method. A Ru(0001) single crystal (MaTeck GmbH, 9 mmφ, 1.5 mm thick) was mounted on a stainless steel sample holder with a 9 mmφ diameter hole for heating the sample from the backside using an electron beam from a W filament. K-type thermocouples were spot welded to the ends of the crystal. The crystal was heated at 1000 K for 10 -6 The Ru(0001) surface was oxidized in 10000000000 mbar O2 and cooled to room temperature under oxygen. An electron beam assisted evaporator (Focus EMT3) was used to oxidize the Ru(0001) surface at 90 K and 1000000000000 in an amount equivalent to forming 4 to 5 monolayers (ML) of In2O3(111). -6 Indium was evaporated onto the oxidized Ru(0001) surface from a Mo crucible filled with In (99.9%, Sigma Aldrich) at mbar O. The temperature of the Ru(0001) was then increased at a rate of 1 K / s and maintained at 673 K during the deposition of a further In2O3 layer. Next, the sample was heated for 10 -6 The crystallinity of the film was improved by oxidation in 1000 mbar O2. The thickness of the In2O3(111) film was about 5 nm. The prepared sample is denoted as "In2O3(111)".

[0087] (Comparative Example 5: Preparation of Untreated Cu-In2O3 Membrane Catalyst) Two electron beam assisted evaporators (Omicron EMT3) were used to co-deposit Cu and In on the In2O3(111) film from Mo crucibles filled with Cu and In, respectively. Approximately 0.1 ML of Cu and 0.9 ML of In were deposited on the In2O3(111) surface. 1.0 ML as used in this application is 1 atom per In2O3(111) surface unit cell, i.e., 5.6 × 10 13 atoms / cm 2 The fluxes of Cu and In were 0.02 ML / min and 0.1 ML / min, respectively. The samples were then -5 The resulting sample was denoted as “untreated Cu-In2O3”.

[0088] (Example 6: Preparation of plasma-treated Cu-In2O3 film catalyst) An untreated Cu-In2O3 film catalyst was prepared in the same manner as in Comparative Example 6. Next, the untreated Cu-In2O3 film catalyst was subjected to non-thermal plasma treatment in the presence of O2 in the manner described below, thereby obtaining a plasma-treated Cu-In2O3 film catalyst, which is represented as plasma Cu-In2O3.

[0089] At an anode voltage of 1 kV and an emission current of 0.5 μA, 7 × 10 -6 Oxygen plasma treatment of the untreated Cu-In2O3 film catalyst was carried out using a microwave plasma generator equipped with a commercial plasma source (OSPrey, Oxford Scientific, Fig. 1a) operated in mbar O2. The duration of the plasma treatment was 1 h.

[0090] (Reference Example 3: Preparation of plasma-treated In2O3 film catalyst) In the same manner as in Example 6, the In2O3 film catalyst of Reference Example 2 was subjected to oxygen plasma treatment.

[0091] (Evaluation of Results) The surface morphology of the In2O3 film catalysts of Reference Examples 2 and 3 was evaluated using STM. The STM image of the plasma-treated In2O3 film catalyst from Reference Example 3 (Figure 5b) revealed the formation of In2O3 clusters with a wide size distribution ranging between 1 and 4 nm in diameter that were randomly distributed on the surface of the plasma-treated In2O3 film catalyst. The number of In2O3 clusters normalized per unit area of ​​the STM image was 0.08 clusters / nm 2 Such In2O3 clusters were not observed in the non-plasma-treated In2O3(111) film catalyst of Reference Example 2 (see FIG. 5a).

[0092] The XPS O1s spectrum of the (Cu-)In2O3 catalyst revealed that a shoulder appeared after plasma treatment (Figure 6). This shoulder was due to defect sites ("O defect This result was consistent with the STM images, in which plasma treatment produced more clusters, providing a strong shoulder in the O1s spectrum.

Claims

1. A catalytically active material comprising a metal oxide doped with a doping metal, The metal oxide is CeO 2 , ZnO, Ga 2 O 3 , In 2 O 3 , ZrO 2 , Fe 2 O 3 , Al 2 O 3 is selected from the doping metal is selected from Cu, Pd, Au; The catalytically active material is obtainable by a process including a non-thermal plasma treatment step.

2. The metal oxide is In 2 O 3 2. The catalytically active material of claim 1, wherein

3. 2. The catalytically active material of claim 1, wherein the doping metal is Cu.

4. 2. The catalytically active material according to claim 1, wherein the content of the doping metal relative to the metal oxide is from 0.01 wt% to 5.0 wt%, preferably from 0.01 wt% to 3.0 wt%, more preferably from 0.05 wt% to 0.3 wt%.

5. 10. The catalytically active material of claim 1 in the form of particles.

6. 6. The catalytically active material of claim 5, wherein the catalytically active material is composed of the metal oxide, the doping metal and any negatively charged counter ions.

7. 6. The catalytically active material of claim 5, wherein the catalytically active material has an average particle size of 5 nm to 50 nm as measured by transmission electron microscopy or scanning transmission electron microscopy.

8. 10. The catalytically active material of claim 1 in the form of a membrane.

9. H 2 and CO 2 CO by reacting a gas mixture consisting of 2 2. Use of the catalytically active material according to claim 1 in the catalytic hydrogenation of to methanol.

10. H 2 and CO 2 The use according to claim 9, wherein the mixed gas comprising is reacted in the presence of the catalytically active material at a pressure of 10 bar to 150 bar and at a reaction temperature of 100°C to 400°C, preferably 150°C to 350°C.

11. The mixed gas has a H 2 / CO 2 10. The use according to claim 9, having a molar ratio.

12. A method for producing a catalytically active material according to any one of claims 5 to 7, comprising the steps of: (1) Add an alkaline solution (e.g., Na 2 CO 3 co-precipitating the doping metal and the metal component of the metal oxide as a hydroxide precipitate by adding a hydroxide solution to the solution; (2) washing and drying the precipitate; (3) O 2 and calcining in the presence of (4) subjecting the calcined precipitate to a non-thermal plasma treatment to obtain particles of the catalytically active material; The method comprising:

13. The method of claim 12 , wherein the non-thermal plasma treatment is carried out at a pressure of 40 mbar or less.

14. A method for producing the catalytically active material of claim 8, comprising the steps of: (1) providing a film comprising a metal of said metal oxide and said doping metal, preferably by a co-deposition method; (2) annealing the film in the presence of oxygen; (3) performing a non-thermal plasma treatment; The method comprising:

Citation Information

Patent Citations

  • A substrate surface composed of heat-resistant metal alloy nanoparticles, a method for preparing the same, and its use, in particular, as a catalyst.

    JP2014529354A

  • Substrate surface structured with thermally stable metal alloy nanoparticles, a method for preparing the same and uses thereof, in particular as a catalyst

    US20140193745A1

  • Catalyst for methanol production, method of producing the same and process of methanol production

    US20150111975A1

  • Catalyst for methanol production, method for producing same, and method for producing methanol

    WO2013183577A1